The Evaluation of Ecoprint Training for Female Inmates at The Class IIA Women’s Correctional Institution in Semarang: Evaluasi Pelatihan Ecoprint pada Narapidana Perempuan di Lapas Perempuan Kelas IIA Semarang - Titik Ekowati; Dhian Saraswati; Wulan Sumekar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The rehabilitation of inmates faces challenges in providing training due to limited time. This prompted the implementation of ecoprint training, which has a short production time. The purpose of this study is to evaluate ecoprint training using tea for inmates. The method used is action research, with a total of 30 female inmate respondents. The analysis employed is the Wilcoxon Signed-Rank Test and N-gain test. The results showed a significant difference between pretest and posttest in knowledge, with an average increase of 0.94, classified as high. A total of 93% of the respondents, or 28 out of 30 participants, fell into the high category. This indicates that the tea-based ecoprint training is highly effective in increasing the knowledge of inmates.